Criteria to assess efficiency: Psychoanalysts, cognitive behavioral, rational emotive behavior, and psychoanalytical therapists speak up - Mantilla Lagos, Carla Eugenia (2006)
The article explores the criteria used to assess the efficiency of individual psychotherapeutic treat-ments with adults. In doing so it used the perspective of 40 professionals that represent 4 types of clinical interventions: cognitive behavioral, psychoanalytic, rational emotive psychotherapies, and psychoanalysis. In addition, it seeks to identify the similarities and differences among these with regards to above-mentioned criteria. A semi-structured interview was built and applied, exploring considerations on the efficiency of the treatments. The qualitative analysis resulted in twelve analysis topics and its corresponding answer categories. These were analyzed through descriptive and correspondence statistics. These criteria are numerous and highly variegated. Differences among the 4 groups are related to the nature of each therapeutic focus and its underlying theoretical paradigm. Psychoanalysts and cognitive behavioral therapists are the groups that aremost differentiated between each other.